Novel Experimental Agents for the Treatment of Hypercholesterolemia - Pećin I; Reiner Ž (Dove Medical Press, 2021)
Ivan Pećin,1,2 Željko Reiner1,2 1Zagreb School of Medicine, University of Zagreb, Zagreb, Croatia; 2Division of Metabolic Diseases, Department of Internal Medicine, University Hospital Center, Zagreb, CroatiaCorrespondence: Željko ReinerDivision of Metabolic Diseases, Department of Internal Medicine, University Hospital Center Zagreb Kispaticeva 12, Zagreb, 10 000, CroatiaTel + 385 1 2388772Fax + 385 1 2388623Email zreiner@kbc-zagreb.hrAbstract: Atherosclerotic cardiovascular diseases (ASCVD) are still the leading cause of morbidity and mortality in most developed countries and even more in developing countries. Dyslipidemia is a well known main risk factor for ASCVD. Lipid-lowering treatment, particularly lowering LDL-cholesterol (LDL-C), can decrease the risk for ASCVD. New data and guidelines based upon them suggest that we should go with LDL-C levels as low as we can. Therefore, conventional lipid lowering agents (statins and statins+ezetimibe) are not enough mainly because of poor compliance and statin intolerance which is in the real world mostly pseudo-intolerance. PCSK9 inhibitors provided a new hope to further decrease LDL-C but are still expensive, they have to be injected subcutaneously twice a month and their long-lasting adverse effects are not known. Therefore, there is a constant need to develop novel, more potent, more safe, less expensive, more user friendly regimens of hypolipemic agents (bempedoic acid, selective PPAR alpha receptor modulators etc). One of the ways to overcome poor compliance and increase the potency of therapy with less adverse effects are fixed combinations of established drugs (statin+ezetimibe). The future of hypolipemic agents is based on antisense therapy, ie. the use of specific oligonucleotide sequences blocking the translation of the selected protein (targeting apolipoprotein CIII, lipoprotein (a), apolipoprotein B) or RNA silencing technique (PCSK9 mRNA) and are in various stages of clinical trials. Some of them are almost ready to use in everyday clinical practice. High risk and very high risk patients (eg. familial hypercholesterolemia, familial severe chylomicronemia syndrome) will benefit most. The aim of this review is to inform about novel hypolipemic agents – potent and safe drugs for dyslipidemia which should reduce the risk of ASCVD.Keywords: dyslipidemia, novel hypolipemic drugs, cardiovascular risk, LDL-cholesterol, triglycerides, inclisiran, PCSK9 inhibitors, pemafibrate, bempedoic acid, ANGPTL3, pelacarsen